Facile fabrication and photocatalytic properties of ZnO nanorods/ZnSe nanosheets heterostructure. (July 2015) - Liu, Xiaoyan; Cao, Jian; Feng, Bo; Yang, Lili; Wei, Maobin; Zhai, Hongju; Liu, Huilian; Sui, Yingrui; Yang, Jinghai; Liu, Yaohui
Highlights: We have successfully fabricated ZnO nanorods/ZnSe nanosheets heterostructure. The evolution of structural, optical and photocatalytic properties of samples was investigated. The heterostructures showed much higher photocatalytic activities than bare ZnO NRs. The photocatalysis mechanism of the heterostructure was systematically illuminated. Abstract: The ZnO nanorods/ZnSe nanosheets heterostructure had been successfully fabricated by the spin coating method. The evolution of the structural, optical and photocatalytic properties of the samples with different spin coating times was comprehensively investigated. The X-ray diffraction (XRD) patterns showed that the relative intensities of ZnSe peaks increased gradually with the increase of spin coating times, but the ZnO peaks were relatively suppressed, which had a good agreement with the results of Raman spectra. The scanning electron microscope (SEM) and transmission electron micrograph (TEM) images further confirmed that the ZnSe nanosheets (NSs) had been successfully assembled on the top surfaces of the ZnO nanorods (NRs) and in the upper parts of the gaps between the rods. At room temperature, the ZnO/ZnSe heterostructures exhibited a relatively suppressed UV emission together with a dramatically enhanced deep-level emission. In addition, the heterostructures exhibited remarkable photocatalytic activities. The type-II staggered band alignment and defects formed at the ZnO/ZnSe interfaces should be the key factors for improved photocatalytic performance, and the probable photocatalytic mechanism was discussed in detail.